ELECTROHYDROCYLINDER OF INCREASED EFFICIENCY: PROSPECTS FOR THE DEVELOPMENT OF MECHATRONIC SYSTEMS - A. E. Karamguzhinova (Вестник СибАДИ, 2020)
Introduction. The problem of increasing the efficiency of power machines is important to develop a new design of the main elements or drive with the possibility of widespread use of hybrid drives. To preserve the power characteristics of the drive and its technical and operational indicators, the authors consider a hybrid with the available electric and hydraulic drive parts that form a complex synergistic mechanism as an alternative. The proposed combined tracking system with the specified parameters allows for the efficient operation of the drive of many machines.Materials and methods. The paper presented the results of an analytical study, the prospects for the development of mechatronic systems in engineering and technological complexes. The research also identified the industry area with a high development potential for mechatronic and hybrid drives. The authors formulated the problem of designing and developing hybrid drives due to the fact that there was no single method for substantiating the energy efficiency indicators of a power hybrid drive that ensured the interaction of two dissimilar systems (electric drive and hydraulic drive with fundamentally different parameters).Results. Therefore, the authors conducted the analysis of the structural, technological and operational parameters of the hybrid drive systems and proposed a combined servo drive system.Discussion and conclusions. The authors prove and justify the extensive possibilities of using hybrid drives as an alternative to pneumatic and hydraulic drives The results of the research allow specifying the directions and prospects of using hybrid synergetic drives and systems for the functioning of working equipment, machines and complexes.Financial transparency: the authors have no financial interest in the presented materials or methods. There is no conflict of interest.